Public health policies and the challenge faced by the COVID-19 pandemic - França, Kátia Justina Silva; Alves, Celso Gonçalves; Pereira, Élida de Azevedo; Dalbello-Araujo, Maristela (Seven Editora, 2023)
Public policies are state constructions that implement effective mechanisms in society in the search for solutions to the public problem, thus seeking harmony and the reduction of social inequality. Some authors that we will address in the course of the text, affirm that they are inserted in the social actions of the State, promoting well-being, better health conditions to the population and to each individual, going much further than that, reducing social inequalities in health. This article aims to weave a literature review, aiming to gather essential information and data that permeate public health policies and the challenges of the Covid-19 pandemic. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-104